HYDROGENATION OF FURFURAL TO FURFURYL ALCOHOL USING POROUS NICKEL CATALYST - Dzaky Mualim, Ahmad
The hydrogenation of furfural into furfuryl alcohol was catalyzed by porous nickel. Formic acid was used as a hydrogen source. Porous nickel was prepared in 2 steps, i.e., the synthesis of Ni-Al alloys and the removal of AI metal. Ni-Al alloy was prepared by 2 methods, namely hydrothermal and mechanical ball-milling. The hydrothermal method was carried out at 200 oc for 24 h using hydrazine as a reducing agent. The mechanical ball-milling was carried out with a planetary ball mill. The milling was done for 24 h, with a speed of 500 rpm and a powder ratio of 1:20 (75at% Ni) to the ball. The formation of Ni-Al metal alloys was confirmed using XRD. The XRD analysis results show the formation of NbAl species. Yet, Ni(O) metals were still predominantly present in the alloy. The removal of AI was carried out by reacting the alloy with NaOH. The process was carried out at 90 °C for 1 h to produce black solid. The solid was filtered and washed using H20 and ethanol. The porous Ni was dried under vacuum and the result were stored in a nitrogen atmosphere. These porous Ni were employed as a catalyst in the furfural hydrogenation. The catalytic reaction was carried out at 150 oc for 4 h in ethanol or formic acid in the absence of H2. Ethanol or formic acid worked as sources of hydrogen in the hydrogenation. The product was characterized using GC (FID) and 1H NMR. The furfural conversion and product selectivity to furfuryl alcohol was 77% and 66%, respectively when porous Ni prepared hydrothermally was used in the reaction. In contranst, the porous Ni prepared by mechanical milling showed no catalytic activity in this hydrogenation.